Impact of Vertical Void Design on Ventilation Performance of Boarding Houses in Hot Humid Climate - Hakim, Muhammad Naufal; Ekasiwi, Sri Nastiti Nugrahani; Samodra, FX Teddy Badai (Nature: National Academic Journal of Architecture, 2025)
Vertical voids can enhance the performance of natural ventilation, improving physiological cooling and indoor air quality (IAQ), particularly in boarding houses as shared living spaces. The effect of void design on ventilation is influenced by various design variables, such as the proportion of openings, the void-to-building ratio, the void aspect ratio, and the void’s position within the building. The effects of vertical void towards ventilation efficiency can be improved by modifying these variables. This study investigates the impact of these design variables on ventilation performance through field surveys and microclimate measurements. Descriptive statistical methods were used to analyze the effects of different designs on two boarding houses. The results of the study can be considered in low-rise housing design as a way to improve natural ventilation performance. The findings show that CO2 concentrations remain stable at 400–600 ppm, which is attributed to low occupancy levels and large void volumes, regardless of the void design or air velocity. Airflow as an indicator of physiological cooling varied between day and night, with daytime ventilation being more effective on upper floors due to stronger thermal buoyancy and wind speeds. Nighttime ventilation was less effective, with weaker airflow, especially on the upper floors, affecting physiological cooling. Adjusting the void’s aspect ratio can improve natural ventilation performance; narrower voids enhance upward airflow at night, while larger aspect ratios improve ventilation during the day.